Penetrating injury of the lungs and multiple injuries of lower extremities caused by aircraft bombs splinters - Golubović Zoran; Stanić Vojkan; Trenkić Srbobran; Stojiljković Predrag; Stevanović Goran; Lešić Aleksandar; Golubović Ivan; Milić Dragan; Višnjić Aleksandar; Najman Stevo (Vojnosanitetski Pregled)
Introduction. Injuries caused by aircraft bombs cause severe damages to the human body. They are characterized by massive destruction of injured tissues and organs, primary contamination by polymorph bacterial flora and modified reactivity of the body. Upon being wounded by aircraft bombs projectiles a victim simultaneously sustains severe damages of many organs and organ systems due to the fact that a large number of projectiles at the same time injure the chest, stomach, head and extremities. Case report. We presented a patient, 41 years of age, injured by aircraft bomb with hemo-pneumothorax and destruction of the bone and soft tissue structures of the foot, as well as the treatment result of such heavy injuries. After receiving thoracocentesis and short reanimation, the patient underwent surgical procedure. The team performed thoracotomy, primary treatment of the wound and atypical resection of the left lung. Thoracic drains were placed. The wounds on the lower leg and feet were treated primarily. Due to massive destruction of bone tissue of the right foot by cluster bomb splinters, and impossibility of reconstruction of the foot, guillotine amputation of the right lower leg was performed. Twelve days after the wounding caused by cluster bomb splinters, soft tissue of the left lower leg was covered by Tirsch free transplantant and the defect in the area of the left foot was covered by dorsalis pedis flap. The transplant and flap were accepted and the donor sites were epithelized. Twenty-six days following the wounding reamputation was performed and amputation stump of the right lower leg was closed. The patient was given a lower leg prosthesis with which he could move. Conclusion. Upon being wounded by aircraft bomb splinters, the injured person sustains severe wounds of multiple organs and organ systems due to simultaneous injuries caused by a large number of projectiles. It is necessary to take care of the vital organs first because they directly threaten the life of the wounded patient. Despite adequate surgical treatment of war wounds of the feet, because of massive defect of bone and soft tissue, amputation may be the only rational solution of the treatment. The resection of the lung may be successful method for the severe destruction of the lung.